PROBLEM ETIK DALAM HUKUM POSITIF - Ari Purwadi (Perspektif, 2007)
Ethics refer to desirable conduct. Detemerning what is desirable conduct in a given situation depends on what values one follows. The value recommend to guide in positive law Jurisprudence is the study of values concerning law and legal systems. Schools of jurisprudence present different values for judging whether positive law is appropriate ethical conduct.